Seroprevalence of Rickettsial disease: A population-based survey from kashmir valley, North India - Bashir Ahmad Fomda; Asiya Khan; Yaawar Bashir Mir; Sehrish Baqal; Anis Bashir Fomda; Rauf Ur Rashid Kaul (Indian Journal of Public Health, 2023)
Background: Limited studies have been done regarding the prevalence of Rickettsial diseases in India and as far as UT of Jammu and Kashmir is concerned, only a few hospital-based studies are available. Objectives: The present study was therefore planned to find the seroprevalence of Rickettsial diseases in Kashmir Valley. Materials and Methods: A multistage sampling procedure was used for the collection of samples from 10 districts of Kashmir Valley and a total of 1740 samples were collected. In addition, 802 healthy blood donors were included to establish baseline titers for Weil–Felix (WF) Test. Results: Of 1734 subjects, 73 were positive by the WF test. The overall seroprevalence of Rickettsial diseases was 4.1% with the highest prevalence of scrub typhus (2.30%) followed by the spotted fever group (1.5%) and typhus group (0.40%). Maximum seropositive subjects were from district Kulgam (6.97%) followed by Pulwama (5.92%), Shopian (5.79%), Anantnag (5.47%), Ganderbal (5.00%), Kupwara (4.72%), Baramulla (4.62%), Srinagar (2.63%), Bandipora (2.41%), and Budgam (0.54%), respectively. Seropositivity was higher in females and subjects who had contact with ticks and mites like those involved in the collection of firewood and grass or had contact with uncut grass or shrub. The seropositivity was also significantly higher in those working in paddy fields and those living near the forest (P < 0.05). Conclusion: The results of the present study confirm the existence of Rickettsial diseases in this region. This data would promote awareness of rickettsioses among local physicians and will also serve as a baseline to detect changing prevalence in the future.